Synthesis of Nitrogen containing liner polymer - Kurdia, Siddharth Kumar (IISERM, 2019)
Various type of polyesters have been studied in past years. Methods used for the preparations are, esterification, transesterification, Acylation and Ring opening polymerization etc. We have focused to synthesize N-containing polyesters by using melt-transesterification conditions In our current study, we set our goal towards synthesizing two ‘AA’ type monomers 2,6- pyridine dicarboxylic acid, 2,6-diethyl ester (M 1) and 2,6-pyridine dicarboxylic acid, 2,6-diethyl ester (M 2) followed by polymerization of these monomers with Hexanediol (BB type) via melt transesterifications. Resulting polymers are named as Polymer 1 and Polymer 2 respectively as per our observation the polymer 1 has a higher kinetic rate relative to the polymer 2. The synthesis and kinetic studies of these two polymers have discussed in this report.
Keywords: Chemistry; Polyester; Polymers; Melt-Transesterification; Synthesis of 1,3-Benzenedicarboxylic acid